Skill level and the free moment during a pistol aiming task - Ko, J. H.; Han, D. W.; Newell, K. M. (Sports Biomechanics, 2024)
The present study investigated the transversal rotation of body and its relation to the horizontal movement for expert shooters and novices in a pistol aiming task. Participants stood on a force plate with an air pistol and aimed it to the centre of a target, positioned 1.4 m above the floor and 10 m away from the force plate, for 30 s as accurately as possible. The results revealed that the novice group showed greater transversal body variability represented by the free moment (FM) than the expert group. Correlation analysis showed that there is tight coupling between the FM and centre of pressure both in the anterior-posterior and medio-lateral directions for the expert group while only strong coupling of that in the anterior-posterior direction for the novice group. The findings suggest that FM is a critical factor to accurately aim the pistol on the target and there is a different postural strategy, in terms of the body motion in the transversal and horizontal space, as a function of skill level to realise success in the pistol aiming task.